HUBUNGAN KONSUMSI KOPI, KONSUMSI SERAT DAN TINGKAT STRES DENGAN KUALITAS TIDUR PADA ORGANISASI KARANG TARUNA DI RW 02 PONDOK LABU - Aisah Rahmawati (2020)
Late adolescence is a transition to early adulthood. In this phase there is an increase in activity and it requires sufficient sleep. Sleep is the time needed to rest, strecth tensed muscles and recover the energy after a day full of activities. Sleep quality is an individual's statisfaction with sleep. The purpose of this study was to determine the relationship of coffee consumption, fiber consumption and stress level with sleep quality in Karang Taruna Organization in RW 02 Pondok Labu. This is a cross-sectional study with a sample of 54 respondents selected by convenience sampling. Sleep quality data was assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, coffee consumption data was assessed using a coffee consumption questionnaire, fiber consumption data was assessd using the Semi-Quantitative Food Frequency Questionare (SQ-FFQ), and stress level data was assessd using the Perceived Scale Stress-10 questionnaire (PSS-10). Analysis of the relation was performed using the chi-square test. The results showed no significant relationship between coffee consumption (p = 1,000), fiber consumption (p = 1,000) and stress level (0.890) with sleep quality. The conclusion obtained in this study were there was no significant relationship between coffee consumption, fiber consumption, and stress level with sleep quality.